Marketing Strategy For Postal Services Using Servqual And Importance–Performance Analysis (IPA) To Improve Market Competitiveness At Pt. Pos Indonesia Tulungagung - Fauziah, Siska Arifah; Azizah, Nurul (UNIVED Press, 2026)
This study aims to analyze the marketing strategies of PT. Pos Indonesia Tulungagung in enhancing its market competitiveness amidst the growing competition in the logistics service industry. The research employs a qualitative descriptive approach by integrating the SERVQUAL method with Importance–Performance Analysis (IPA). SERVQUAL is applied to identify the gap between customers’ expectations and their perceptions of postal services across five key dimensions: reliability, assurance, tangibles, empathy, and responsiveness. Meanwhile, IPA is utilized to map service attributes based on their level of importance and actual performance, enabling a more precise determination of improvement priorities. The findings reveal that reliability and responsiveness are the most critical factors requiring enhancement, particularly in terms of delivery timeliness and customer complaint handling. The implementation of strategies focused on improving service quality, employee training, technological innovation, and continuous monitoring of customer feedback has proven effective in increasing customer satisfaction and loyalty, thereby strengthening the competitive position of PT. Pos Indonesia Tulungagung in the market.